ASSESSING THE ROLE OF INFRASTRUCTURE AND PUBLIC HEALTH INTERVENTIONS IN IMPROVING SANITATION FACILITY USAGE IN FLOOD-PRONE AREAS OF TSHOLOTSHO DISTRICT - Mathura, M; Kitagawa, J. A; Tidwell, Dr A (International Journal of Allied Sciences (IJAS), 2023)
This paper examines the significant WASH-related difficulties in Africa that claim many lives. Sanitation-related infections are the second leading causes of infant mortality in Africa after pneumonia and malaria. The study aims to explore the factors determining sanitation facility use in Tsholotsho District, Zimbabwe. A quantitative approach was used to collect data from 218 respondents in four wards through questionnaires. Access to treated water, age, household income, and distance from the nearest water source were identified as the significant factors that influenced the selection of a sanitation facility. The study recommends the need for more initiatives aimed at solving rural WASH challenges in Africa, especially ending open defecation.